PENGARUH ASSET COMPOSITION, FINANCIAL LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI - Tisa Aisyah (2017)
The study was conducted to examinie the effect of asset composition, financial leverage and firm size on tendency of accounting fraud. The research was conducted by quantitative methods using secondary data. Secondary data comes from a list of case OJK (Otoritas Jasa Keuangan) and the company's annual report listed in Indonesia Stock Exchange as sample. Sampling technique using purposive sampling (purposive sampling method). Selection of as sample of 44 real estate companies listed in Indonesia Stock Exchange in 2013 until 2015 resulted in 39 companies that are acceptable. Testing the hypothesis in this study using multiple Logistic Regression Analysis with SPSS 23 and a significance level of 5%. The results of the testing showed that : (1) asset composition has significant influence on the tendency of accounting fraud with a significance level of 0,020 is smaller than the specified level α = 0,05. (2) financial leverage has no significance effect on the tendency of accounting fraud because it has a significance level of 0,069 is greater than the specified level α = 0,05. (3) firm size has no significance effect on the tendency of accounting fraud because it has a significance level of 0,171 is greater than the specified level α = 0,05.